The rabbit gingival tissue response to retraction liquids and tetrahydrozoline - Kostić, Ivan; Mihailović, Dragan; Najman, Stevo; Stojanović, Sanja; Kostić, Milena (Vojnosanitetski pregled, 2013)
Backround/Aim. Retraction agents for temporary vertical and lateral suppression of gingival tissue as well as bleeding control and fluid flow in the gingival sulcus are expected to have maximal efficiency without irreversible damage of local tissue and adverse systemic effects. The research started from the assumption that tetrahydrozoline is a biologically more acceptable means of gingival retraction than commercially available preparations. The aim of the study was to comparatively analyse the inflammatory effects of different retraction materials and tetrahydrozoline. Methods. The effect of retraction liquid on the basis of aluminum chloride and epinephrine and tetrahydrozoline hydrochloride on gingival tissue of rabbits was investigated. The application time in the rabbit’s gingival sulcus was 7 minutes. Tissue biopsy was performed after an hour, a day, and 7 and 30 days. Tissue preparations were analyzed under a microscope. Results. The obtained results indicate a reversible damage of gingival tissues as a result of local application of aluminum chloride- and epinephrine-based retraction agents. Their use led to acute inflammatory response after an observation period of 1 and 7 days. After 30 days reparation of damaged tissue was observed. The use of tetrahydrozoline resulted in a visibly weaker inflammatory response. Conclusion. Retraction liquids insertion led to an acute inflammatory response of gingival tissue which in time assumed a chronic character. The inflammatory response to the administered tetrahydrozoline was significantly lower with complete reparation of gingival tissue. Taking this fact into account it is recommended as a potential retraction agent.